How to kill the Scrum monster : quick start to Agile scrum methodology and the Scrum Master role - Bibik, Ilya (Apress, 2018)
Implement Scrum or improve how Scrum works in your team or organization using this concise, sharp, and programmatic book. You will quickly learn what you need to know without getting confused with unnecessary details. What You'll Learn: Become familiar with Agile concepts and understand the path from Waterfall to the Agile Manifesto Understand the most commonly used Agile methodology--Scrum--and how it relates to eXtreme Programming and Kanban as well as to Lean principles Identify the challenges of the Scrum Master role and understand what this role is all about Know the stages of Scrum team development Embrace and solve conflicts in a Scrum team.